Creating Brave & Productive Learning Environments for Young Adolescents: Parents’ Perspectives of Teacher-Parent and Teacher-Student Relationships - Leslie Rogers; Dan Hyson (Middle Grades Review, 2022)
Teachers are masters of content and of creating connections (e.g., students-content, students-students, teacher-students, teacher-parents). Both impact one’s ability to create and sustain brave and productive learning environments. Teachers connect students to the content, and to each other. At the top of the list of important connections are teacher-student and teacher-parent relationships. In the current paper, we examine these relationships from the perspective of parents of middle school students with disabilities, an under-studied group. We describe theories of learning that support investigating these relationships from parents’ perspectives and outline why this could be an impactful lens for teachers to consider. We share questions asked and surveys used to better understand teacher-parent and teacher-student relationships from middle school parents’ perspectives and describe the results of eight studies that have focused on parents of students with disabilities. Parents confirmed that teacher-student and teacher-parent relationships are important to their students’ learning. Results also suggest that there are limited reliable measures assessing parents’ perspectives of teacher-student and/or teacher-parent relationships. Implications of these findings for future research and teaching practices are explored.
Keywords: family involvement; middle school; parent perceptions; teacher-parent relationships; teacher-student relationships; school-home partnerships; students with disabilities